Elevated expression of FABP3 and FABP4 cooperatively correlates with poor prognosis in non-small cell lung cancer (NSCLC) - Tang, Zhiyuan (Oncotarget, 2016)
Fatty acid binding proteins (FABPs) are intracellular lipid-binding proteins that are involved in a variety of biological cellular processes, including tumorigenesis. In this study, we explored the expression pattern of FABP3 and FABP4 in non-small cell lung cancer (NSCLC) as well as their roles in prognosis. We determined mRNA expression of FABP3 and FABP4 in matched pairs of cancerous and non-cancerous fresh frozen tissues from 30 NSCLC patients. Tissue microarray immunohistochemical analysis (TMA-IHC) was applied to determine the protein expression of FABP3 and FABP4 in 281 cancerous and 121 matched adjacent non-cancerous tissue samples. Our results showed that both mRNA and protein expression of FABP3 and FABP4 were significantly higher in cancerous tissues when compared to non-cancerous tissues. Furthermore, high expression of FABP3 or FABP4 in NSCLC was significantly associated with advanced tumor node metastasis (TNM) stage and had a negative impact on the overall survival of NSCLC patients. Concurrent high expression of FABP3 and FABP4 was significantly related to TNM stage. In conclusion, our research demonstrated that high FABP3 or FABP4 expression had strong prognostic value for overall survival in NSCLC. Detection of FABP3 and FABP4 cooperatively was helpful to predict the prognosis of NSCLC.